The Legal Lacunae of UNCLOS and CBD to The Access and Benefit Sharing of Marine Genetic Resources in The Area Beyond National Jurisdiction - Sri Wartini (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
This article aims to comprehensively analyze the legal lacunae of UNCLOS and CBD in regulating the utilization and benefit sharing of marine genetic resources (MGRS) in the area beyond national jurisdiction (ABNJ). T he study argues that the existence of international legal instruments, such as the UNCLOS and the CBD fail to regulate the legal status of MGRS in the ABNJ as well as to regulate access and benefit sharing. The debate arises in the legal status of MGRS in the ABNJ will be applied the regime of common heritage of mankind or freedom of the sea, because both regimes have different legal implication. This study is a normative juridical research by applying conceptual and statutory approaches. The result of the study found that it is essential to addressed the legal lacunae in order to maintain equitable benefit sharing in the utilization of MGRS in the ABNJ. Therefore, in order to overcome the legal lacunae of UNCLOS and CBD, it is urgent to create new internationally binding Agreement..